Agenda Setting Rencana Pembangunan Jembatan Bangka-Sumatera: Agenda Setting for the Bangka-Sumatra Bridge Development Plan - Audia, Zilna Monika; Ibrahim, Ibrahim; Sarpin, Sarpin (Journal of Social Contemplativa, 2023)
The research entitled "Agenda Setting for the construction of the Bangka-Sumatra bridge" focuses on several interests from the economic, social, and political sides. The research method in this writing is descriptive qualitative research. The results of the study that Agenda setting is a program carried out by the Bangka Belitung government to solve problems that occur in Bangka Belitung such as inflation in Bangka Belitung which is one of the backgrounds to improve the economy in Bangka Belitung by providing alternative policies such as building the Bahtera Sriwijaya Bridge, where the bridge is 13.5 kilometers long located in Sebagin Village Bangka Belitung. From providing policy alternatives, the Bangka Belitung regional government provides policy actions such as providing policies in long-term development by making Regional Spatial Planning Regulations (PERDA RTRW). Then the results of the policy cannot be implemented properly due to budget constraints because the construction of the bridge requires a very high budget, then the community is also still thinking about the negative impact of the bridge later such as crime, culture and traffic accidents. Since the feasibility test was carried out until now there has been no significant process for the bridge. This means that development in the region requires an agenda setting that must look at the side of economic interests, social interests and political interests in it.